SPATIAL DISTRIBUTION AND SOURCE IDENTIFICATION OF HEAVY METAL POLLUTION IN URBAN RIVER SEDIMENTS: A CASE STUDY FROM THE ACAI RIVER, JAYAPURA, PAPUA - Bungasalu, Benny Abraham; Anou, Kezia Noviani; Sinaga, Ego Srivajawaty; Ngaderman, Hubertus; Martina Bunga; Maikson Molama (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
The Acai River is a river that flows through densely populated areas, from households and salons to small industries such as tofu and tempeh factories. The community's waste disposal into the river pollutes the river. Studies and monitoring of river quality, especially in Indonesia, are still dominated by examining pollutant levels in river water. However, sediment is also important for in-depth study. This study aims to examine the spatial distribution of heavy metals in sediments in the Acai River located in the urban area of Jayapura, Papua Province. Sediment samples were taken from five locations representing areas with different anthropogenic activities, such as dense settlements, home industries, and small business areas. Then, the samples were dried by placing them in an oven at 100°C. Laboratory analysis was conducted to determine heavy metal levels using the XRF (X-ray Fluorescence) method. Results showed the highest Zn concentration reached 102.1 ppm in the downstream location, while Cr and Ni also showed significant accumulation at certain points. The distribution of heavy metal levels did not show a linear pattern along the river flow, indicating local contributions from human activities. These findings confirm that heavy metal pollution in urban rivers is more influenced by local inputs than by the river flow itself.